Estudos proteômicos e metabolômicos em animais frente à exposição à 2,3-butanodiona - Jedlicka, Leticia Dias Lima [UNIFESP] (2016)
The 2,3-butanedione is widely used as flavoring in the food industry and in the electronic cigarette industry, but is also produced by the organisms through the oxidation of sugars, proteins and lipids. Exposure to 2,3-butanedione is associated with several types of diseases, particularly in lung. In this work were administrated 540 mg/kg/day of 2,3-butanedione, by gavage, in Wistar rats and also offered 2,3-butanedione in the drinking water for mice C57/Bl in different concentrations (0, 100, 300 and 500 mg/kg/day), simulating human ingestion. In the lung tissue of Wistar rats were performed histological analyzes, bronchoalveolar lavage and proteomic analyzes. Additional tools were used to verify oxidative stress (determination of carbonyls compounds) and Western blotting to confirm the increase of protein acetylation. In the C57/Bl mice treated with different concentrations of 2,3-butanedione were performed metabolomic analysis in plasma sample and determination of peroxynitrite plasmatic concentrations and the final SOD activity. In the hepatic tissue of the mice were performed determination of GSH/GSSG (reduced glutathione / oxidized glutathione), MGO (methylglyoxal) and histological analyzes. Histological changes were observed in the lung tissue of Wistar rats and inflammation in this tissue was confirmed by the increase of neutrophils and prostaglandins E2 in the bronchoalveolar lavage of the animals of the group treated with 2,3-butanedione. These animals also showed changes in protein profile, increase in protein carbonyl concentration and increase in protein acetylation compared to control group. The mouse groups, control mouse and treated with the different concentrations of 2,3-butanedione, were observed changes in the metabolic profile. Were observed increased in plasma concentrations of peroxynitrite and decrease in the final activity of SOD. Also, were observed, in the hepatic tissues of the mice, a decrease in the concentration of MGO (methylglyoxal) and the GSH/ GSSG ratio (reduced glutathione/oxidized glutathione). However, did not observe alterations in hepatic tissue of the 2,3-butanedione treated mice. From these results, it was possible to confirm that the intake of 2,3-butanedione by Wistar rats can promote alterations in the protein profile, lead to oxidative stress and contribute to the generation of acetyl radical, capable of promoting post-translational protein acetylation, which can lead to lung function impairment. The 2,3-butanedione ingestion leads to changes on the metabolic profile in mice C57/ Bl and there was a differentiated response between males and females after treatment with 2,3-butanedione. The mice C57/Bl also presented an imbalance of antioxidant and pro-oxidant substances in the plasma and hepatic tissues, but did not present histological alterations in the hepatic tissue. We expect to help answer some biologically relevant issues by proposing a non-enzymatic mechanism for the acetylation of proteins and relating it to protein expression and metabolic exposure of 2,3-butanedione.